Analysis and Implementation of Computer Network at PT XYZ to Improve the Efficiency of Interdepartmental Communication - Akhyar, Iscan Nul; Rizqi, Muhammad; Barokah, Nova Rizki; Fahlevi, Muhamad Fahdhan; Eriana, Emi Sita; Hidayat, Imam (PT FORMOSA CENDEKIA GLOBAL, 2025)
In the era of modern technology, the development of communication and computer networks plays an important role in supporting the efficiency and productivity of the company. This research was conducted at PT XYZ, which currently faces several obstacles in the available communication network. This research aims to design and analyze a more effective and efficient communication system and computer network to increase company productivity. The research method used is descriptive qualitative, with systematic steps in understanding empirical phenomena related to computer networks. The network design process is done through simulation using Cisco Packet Tracer, which allows testing the network topology before real implementation, thus reducing costs and risk of damage. The results show that the designed network design can overcome the existing communication constraints at PT XYZ. The simulation ensures that the network device configuration is running optimally, characterized by successful ping results and satisfactory connectivity testing. The use of Cisco Packet Tracer in this research helps in visualizing the network topology, simplifying analysis, and ensuring configuration according to company needs.